Likely Introduction Date of Schmallenberg Virus into France According to Monthly Serological Surveys in Cattle. Issue 5 (11th December 2013) - Zanella, G.; Raballand, C.; Durand, B.; Sailleau, C.; Pelzer, S.; Benoit, F.; Doceul, V.; Zientara, S.; Bréard, E.
Summary To estimate the date of introduction of Schmallenberg virus (SBV) into France, the prevalence of antibodies against the virus was determined monthly in cattle from two northern departments from August 2011 to April 2012. Seropositive cattle were detected from October 2011 in both departments with a prevalence of 55.6% in the westernmost department (Meurthe‐et‐Moselle) and of 12.7% in the easternmost department (Manche). Schmallenberg virus seroprevalence then increased rapidly to high levels.